2018
DOI: 10.1080/21541248.2018.1495008
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cdc42 with the anticancer compound MBQ-167 inhibits cell polarity and growth in the budding yeast S. cerevisiae

Abstract: The Rho GTPase Cdc42 is highly conserved in structure and function. Mechanical or chemical cues in the microenvironment stimulate the localized activation of Cdc42 to rearrange the actin cytoskeleton and establish cell polarity. A role for Cdc42 in cell polarization was first discovered in the budding yeast Saccharomyces cerevisiae, and subsequently shown to also regulate directional motility in animal cells. Accordingly, in cancer Cdc42 promotes migration, invasion, and spread of tumor cells. Therefore, we ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…MBQ-167 treatment of TNBC, HER2 (þ) breast, gastric, pancreatic, and ovarian cancer and neuroblastoma, as well as yeast cells that are dependent on Cdc42 for cell polarity, result in a loss of cell viability and polarity and detachment from the substrate (12,16). This phenotype is demonstrated in Fig.…”
Section: Mbq-167 Inhibits Rac and Cdc42 Activation And Viability Of T...mentioning
confidence: 89%
“…MBQ-167 treatment of TNBC, HER2 (þ) breast, gastric, pancreatic, and ovarian cancer and neuroblastoma, as well as yeast cells that are dependent on Cdc42 for cell polarity, result in a loss of cell viability and polarity and detachment from the substrate (12,16). This phenotype is demonstrated in Fig.…”
Section: Mbq-167 Inhibits Rac and Cdc42 Activation And Viability Of T...mentioning
confidence: 89%
“…In recent years, MBQ-167 has been designed to form H bonds with the Asn39 side-chain of Cdc42 and Rac and Asn39 replacement leads to loss of GEF binding [146]. Surprisingly, MBQ-167 inhibits Cdc42 activation with an IC 50 of 78 nmol/L, which make it one of the most effective Cdc42 inhibitors at present [151,152]. MBQ-167 has been shown to inhibit a large proportion of Cdc42 downstream effectors, like PAK and LIMK.…”
Section: Current Research Advances Of Cdc42-targeted Therapies In mentioning
confidence: 99%
“…MBQ-167 can inhibit nearly all Cdc42-induced tumor processes in breast cancer, including cell polarity, cell cycle progression, apoptosis and metastasis [152]. However, MBQ-167 only inhibits Cdc42 activity in breast cancer cells that undergo EMT, rather than non-cancer cells or cancer cells without EMT [151].…”
Section: Current Research Advances Of Cdc42-targeted Therapies In mentioning
confidence: 99%
“…MBQ-167 dually inhibits the activation of both GTPases, with half-maximal inhibitory concentrations ( IC 50 ) of 0.1 μM and 0.08 μM for Rac and Cdc42, respectively. Preclinical studies have shown that MBQ-167 inhibits breast cancer cell migration, viability, tumor growth, and metastasis in vivo without apparent toxicity [ 18 , 24 ]. Currently, this compound is being developed for clinical applications as a potential anti-metastatic therapeutic.…”
Section: Introductionmentioning
confidence: 99%